ARCHITECTURE STUDIO SPACE ANALYSIS OF ENGINEERING FACULTY, SUBANG UNIVERSITY - rosyd rosyadi; Ilhamdaniah Ilhamdaniah (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2021)
The Architectural Design Studio Room, Faculty of Engineering, University of Subang is a room with a large intensity of use, the core activities of the studio start from carrying out the design planning process, making design concepts such as drawing concept sketches, then making pre-design drawings and detailed drawings to make design presentations such as mock-ups and poster. architectural design studio space design needs to accommodate the various activities it contains. Today, many students prefer to work on this course elsewhere rather than in the studio. As a result, the use of studios becomes less effective and has an impact on the condition of the studio which is empty of students. The use of the studio is greatly influenced by the quality of the studio space itself, starting from architectural components such as lighting, ventilation, and the carrying capacity of the furniture as well as the condition of the interior wall color of the studio space. The quality of this space can be seen from the level of student attendance, and the intensity of students being in the studio. This critique aims to find out how much influence the quality of space has on the effectiveness of space use, in this case, the design studio space in the architecture department. and it is hoped that the process of making changes or adding facilities that are able to accommodate all lecture activities and be able to provide lecture facilities that are comfortable and accommodate lecture activities. study program in the Department of Architecture. the carrying capacity of the furniture and the condition of the interior wall color of the studio space. Keywords: Quality Standards, Subang University, Architectural Studio